2017
DOI: 10.1525/as.2017.57.3.475
|View full text |Cite
|
Sign up to set email alerts
|

The Waning Effect of China’s Carrot and Stick Policies on Taiwanese People

Abstract: To repress growing regional/national identity in Taiwan, China applies rationalist strategies, including economic incentives and military threats. Analysis of the Taiwan National Security Survey in 2003–2015 shows that China’s carrot and stick policies negatively correlate with exclusive Taiwanese identity. In younger generations, perception of the strength of the policies is similar, but their effect on identity is weaker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The third venue of research is how the withering of the 1992 Consensus would influence the US-China-Taiwan triangular relationship? In our sample, the younger generations were much likely to perceive the 1992 Consensus as a country-to-country agreement, which may be attributed to their Taiwanese identity (Wang, 2017) or lack of interest in the (re)unification. If this result is due to a cohort effect, then our results may suggest that the negotiation space between China and Taiwan under the 1992 Consensus may be narrower as time goes by.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…The third venue of research is how the withering of the 1992 Consensus would influence the US-China-Taiwan triangular relationship? In our sample, the younger generations were much likely to perceive the 1992 Consensus as a country-to-country agreement, which may be attributed to their Taiwanese identity (Wang, 2017) or lack of interest in the (re)unification. If this result is due to a cohort effect, then our results may suggest that the negotiation space between China and Taiwan under the 1992 Consensus may be narrower as time goes by.…”
mentioning
confidence: 87%
“…On the contrary, only 15% of the respondents made similar comments about the PRC. In another study, analyzing 2002-2016 TNSS surveys, Wang (2017) found that the younger generations in Taiwan identified themselves as "Taiwanese" for non-materialistic reasons. Both studies help explain why the country-to-country explanation of the Consensus enjoyed high levels of support in our study.…”
Section: Public Support For Different Version Of the 1992 Consensusmentioning
confidence: 99%
“…On the other hand, Beijing has not been in control of identity formation on the other side of the Strait. Whereas during the martial law era the Nationalist government emphasised the Chinese cultural roots and identification with a territory that included both China and Taiwan under the control of the Republic of China, as Taiwan began its process of democratization significant changes occurred with regard to how citizens of Taiwan framed their national identity (Bairner and Hwang, ; Hao, ; Wang, ; Wilson, ). From an inclusive identity, by which a majority of Taiwanese people saw themselves as Chinese or Chinese and Taiwanese, an exclusive Taiwanese identity started gradually to emerge in the imagination of the Taiwanese population (Wang, ).…”
Section: Exploring National Identity In the Cross‐strait Contextmentioning
confidence: 99%
“…Whereas during the martial law era the Nationalist government emphasised the Chinese cultural roots and identification with a territory that included both China and Taiwan under the control of the Republic of China, as Taiwan began its process of democratization significant changes occurred with regard to how citizens of Taiwan framed their national identity (Bairner and Hwang, ; Hao, ; Wang, ; Wilson, ). From an inclusive identity, by which a majority of Taiwanese people saw themselves as Chinese or Chinese and Taiwanese, an exclusive Taiwanese identity started gradually to emerge in the imagination of the Taiwanese population (Wang, ). Along with rational factors, such as the cost–benefit assessment that could shape the way individuals framed their national membership, a series of other social and political features, such as generation replacement, life experience related to peacetime, economic development and post‐materialism, as well as a subjective perception of a diminishing significance of the China factor in Taiwan, contributed to the emergence of an exclusively Taiwanese identity.…”
Section: Exploring National Identity In the Cross‐strait Contextmentioning
confidence: 99%
See 1 more Smart Citation